2007
DOI: 10.1371/journal.pone.0000691
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Association Mapping Identifies NELL1 as a Novel IBD Disease Gene

Abstract: Crohn disease (CD), a sub-entity of inflammatory bowel disease (IBD), is a complex polygenic disorder. Although recent studies have successfully identified CD-associated genetic variants, these susceptibility loci explain only a fraction of the heritability of the disease. Here, we report on a multi-stage genome-wide scan of 393 German CD cases and 399 controls. Among the 116,161 single-nucleotide polymorphisms tested, an association with the known CD susceptibility gene NOD2, the 5q31 haplotype, and the recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
1
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 74 publications
(97 reference statements)
1
86
1
8
Order By: Relevance
“…[1][2][3][4] The incidence of IBD is relatively higher in Caucasian than in Asian populations; however, the incidence in Asia is increasing. 5,6 Of the two types of IBD, the genetic contribution to disease risk has been documented more extensively and clearly for CD [7][8][9][10][11][12][13][14][15][16][17] than for UC. [18][19][20][21] So far, linkage and genome-wide association studies have identified more than 30 CD-susceptibility loci in Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The incidence of IBD is relatively higher in Caucasian than in Asian populations; however, the incidence in Asia is increasing. 5,6 Of the two types of IBD, the genetic contribution to disease risk has been documented more extensively and clearly for CD [7][8][9][10][11][12][13][14][15][16][17] than for UC. [18][19][20][21] So far, linkage and genome-wide association studies have identified more than 30 CD-susceptibility loci in Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%
“…HNF4A is predicted to bind a majority of IBD-linked CRRs and to regulate IBD-linked genes (Haberman et al 2014;Meddens et al 2016). Similarly, genetic variants near human HNF4G have been associated with obesity and CD (Franke et al 2007;Berndt et al 2013). Importantly, these diverse roles for HNF4 TFs in host physiology have only been studied in animals colonized with microbiota.…”
mentioning
confidence: 99%
“…Conversely, we did not observe any CD linkage peaks among chromosomal segments that correspond to any of the multiple, highly significant novel associations observed among recent CD genomewide association studies with the exception of NOD2. 33,[35][36][37][38] Notably, for the three most well-replicated associations after NOD2-the IBD5 risk haplotype, IL23R and ATG16L1-the established risk haplotypes or missense variants associated are common in the population and thus the inheritance of risk alleles may frequently come from different founders within a given pedigree weakening potential linkage signals. 33,34 The findings of the present study support the concept that genome-wide linkage and association studies represent complementary approaches to gene identification.…”
Section: Discussionmentioning
confidence: 99%